2010
DOI: 10.1038/nature09128
|View full text |Cite
|
Sign up to set email alerts
|

Sphingosine-1-phosphate is a missing cofactor for the E3 ubiquitin ligase TRAF2

Abstract: TNF receptor-associated factor 2 (TRAF2) is a key component in NF-κB signaling triggered by TNF–α 1,2. Genetic evidence indicates that TRAF2 is necessary for polyubiquitination of receptor interacting protein 1 (RIP1) 3 that then serves as a platform for recruitment and stimulation of IκB kinase (IKK) leading to activation of the transcription factor NF-κB. Although TRAF2 is a RING domain ubiquitin ligase, direct evidence that TRAF2 catalyzes the ubiquitination of RIP1 is lacking. TRAF2 binds to sphingosine ki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

24
662
5
4

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 677 publications
(702 citation statements)
references
References 30 publications
(41 reference statements)
24
662
5
4
Order By: Relevance
“…SphK1-derived S1P regulates pro-inflammatory signaling pathways, including activation of nuclear factor-κB [55]. S1P 1 regulates endothelial barrier integrity as stated above [49][50][51][52]56]; cytokine and adhesion molecule expression, lymphocyte maturation, differentiation and trafficking, and mast cell migration.…”
Section: Modulation Of Leukocyte Functions and Inflammation By S1p Simentioning
confidence: 99%
See 1 more Smart Citation
“…SphK1-derived S1P regulates pro-inflammatory signaling pathways, including activation of nuclear factor-κB [55]. S1P 1 regulates endothelial barrier integrity as stated above [49][50][51][52]56]; cytokine and adhesion molecule expression, lymphocyte maturation, differentiation and trafficking, and mast cell migration.…”
Section: Modulation Of Leukocyte Functions and Inflammation By S1p Simentioning
confidence: 99%
“…The activation of PAR1 in turn stimulates SphK1, S1P export to the cell exterior, 24 and S1P 3 activation, which induces amplification of inflammation by stimulating the production of IL-1 and tissue factor from dendritic cells and disrupting EC barrier function. SphK1 is also implicated in the actions of tumor necrosis factor (TNF) and other cytokines, in which intracellular S1P produced by SphK1 binds to TRAF2 and thereby activates NE-B [55]. Disruption of SphK1 gene alleviates inflammatory diseases including colitis and arthritis, providing further support for the involvement of SphK1 in inflammatory responses [12].…”
Section: Modulation Of Leukocyte Functions and Inflammation By S1p Simentioning
confidence: 99%
“…This is followed by the recruitment of a number of E3 ubiquitin ligases to RIP1, including TNF receptor-associated factor 2 (TRAF2) or TRAF5 and the cellular inhibitor of apoptosis proteins (cIAPs) cIAP1 and cIAP2 resulting in the formation of Complex I. [21][22][23][24] TRAF2 25,26 and cIAPs [27][28][29][30] catalyse the polyubiquitination of RIP1. The ubiquitin-decorated RIP1 is recognized by ubiquitin-binding domain containing proteins in the IkB kinase (IKK) 31 and TAK1 kinase complexes [32][33][34] thus facilitating TAK-1-mediated phosphorylation and activation of IKKs.…”
Section: Rip1 and Tnf Signalling: Inflammation Versus Apoptosismentioning
confidence: 99%
“…2-5 The E3 ubiquitin ligase TRAF2 was the first to be described as being responsible for K63 ubiquitination of RIP1 5-7 together with the lipid shingosine-1-phosphate. 8 Other publications have shown that cIAP1/2 can attach K63 ubiquitin chains to RIP1 [9][10][11][12] or that TRAF2 and cIAPs cooperate for the ubiquitination of RIP1 6,13,14 . These ubiquitin chains bind and associate the TAB/TAK (TAK1/TAB2/TAB3) and NEMO/IKK (IKKa, b, g) kinases complex.…”
mentioning
confidence: 99%